Association Between a Tri-allelic Polymorphism in the Estrogen Metabolism Oxidoreductase NRH:Quinone Oxidoreductase 2 Gene and Risk of Breast Cancer by Molecular Subtype - Zhou, Jiao-Qun; Zhu, Si-Yuan; He, Ye; Yu, Ke-Da (Frontiers in Genetics, 2021)
Background: We hypothesized that NRH:quinone oxidoreductase 2 (NQO2) is a candidate susceptibility gene for breast cancer because of its known enzymatic activity on estrogen-derived quinones. A tri-allelic polymorphism in the NQO2 gene might be associated with the risk of luminal-like breast cancer. Methods: In this case-control study, 2,865 women were recruited, including 1,164 patients with pathologically confirmed breast cancer and 1,701 cancer-free controls. The tri-allelic genetic polymorphism (I-29, I-16, and D alleles) was genotyped by a polymerase chain reaction and restriction fragment length polymorphism (RFLP)-based assay. Because the I-16 allele frequency is rare (approximately 1.0%), individuals carrying the I-16 allele were excluded from the analysis. Breast cancer subtypes were classified according to ER, PR, HER2, and grade. Results: In the association analysis of allele, an increased risk of breast cancer is associated with I-29 allele [82.5% in case group and 79.0% in the control group; odds ratio (OR), 1.25; 95% CI, 1.09–1.43, compared with D allele, p = 0.0015]. In the association analysis of genotype, the I-29-containing genotype was significantly correlated with breast cancer under a dominant model (adjusted OR, 1.31, 95% CI, 1.12–1.54, p = 0.001). Moreover, in the subtype analysis, there was a significant association of the I-29/D polymorphism with luminal-like breast cancer (adjusted OR, 1.54, 95% CI, 1.22–1.94, p = 0.001 for luminal-A disease; adjusted OR, 1.37, 95% CI, 1.06–1.76, p = 0.014 for luminal-B disease) but not with HER2-enriched or triple-negative subtypes. Conclusion: The tri-allelic polymorphism in the NQO2 gene is associated with breast cancer risk, especially for the luminal-like subtype. Our findings provide a new piece of molecular epidemical evidence supporting the hypothesis that estrogen and its metabolites are carcinogens of luminal-like breast cancer. Further external validation studies are needed.